(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
This article examines the vital importance of preserving cultural heritage through modern restoration practices. It provides a comprehensive overview of restoration definitions, emphasizing its relevance in the field of art and architecture. The study details the current state of restoration efforts in Uzbekistan, highlighting the transition from traditional craftsmanship to systematic academic training. Furthermore, the paper discusses the impact of environmental factors on monument degradation and outlines the recent educational reforms and infrastructure developments aimed at fostering a new generation of restoration specialists in the region.